PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MIA 1 SMA PGRI PEKANBARU - Restu Ayu Gustianingrum; Susda Heleni; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve the learning process and to increase mathematics outcomes from the students of class X MIA 1 SMA PGRI Pekanbaru with applied Discovery Learning model. This research is a class action research with two cycle. The subject of this research is the students of class X MIA 1 SMA PGRI Pekanbaru in academic year 2018/2019, which total of participants are 30 students, consists of 15 male students and 15 female students with heterogeneous ability. The instruments used in this research were mathematical learning instruments and the instruments of collecting data. The mathematical learning instruments used include syllabus, lesson plan, and student work sheet, and the instruments of collecting data were observation sheets used to get the teacher and student activity data and learning outcome test used to get mathematics outcome data after learning process. The data analysis techniques used narrative analysis and descriptive statistic analysis. From the analysis of observation sheets, it can be seen that there is improvement of learning process after the discovery learning model being implemented. The data of the student’s evaluation test showed that the students reaches Minimun Mastery Criteria (MMC) of knowledge competency from the basic score to the first test, from the first test to the second test increase from 12 students (40%) become 20 students (66,67%) and increase become 80%. Persentage of students reaches Minimun Mastery Criteria (MMC) of skills competency increase from first test to the second test where the first test 15 students (50%) to the second test 21 students (70%). Based on data analysis, it can be concluded that implementation of discovery learning model can improve learning process and increase student’s mathematics outcome at class X MIA 1 SMA PGRI Pekanbaru in academic year 2018/2019.Key Words: Mathematics Outcomes, Discovery Learning Model, Class Action Research